Methods for building the national science and technology programs in developed countries - Experience and lessons for Vietnam - Tran Anh Tuan; Truong Thu Hang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Recognizing the role of science and technology (S&T) programs, many countries in the world have specific strategies and detailed roadmaps for the process of building their national S&T programs. This article reviews some experiences on the method of building national S&T programs of some developed countries, such as China, Korea, and Taiwan (China)... in the period when those countries had similar socio-economic conditions as our country today. These are some countries and territories with effectively operating S&T program systems, making great contributions to socio-economic development. Based on studying and learning from international experiences, the authors propose some suggestions for applying their lessons to improve the Vietnamese method of building national S&T programs. Code: 24091101